Delaying ACL Reconstruction Beyond 6 months from Injury Impacts Likelihood for Clinically Significant Outcome Improvement. Issue 7 (31st July 2020) - Lu, Yining; Patel, Bhavik; Nwachukwu, Benedict; Beletsky, Alexander; Agarwalla, Avinesh; Chahla, Jorge; Kym, Craig; Yanke, Adam; Cole, Brian; Bush-Joseph, Charles; Bach, Bernard; Verma, Nikhil; et al.
Objectives: A growing number of investigations have demonstrated the negative impact of delaying treatment on clinical and radiographic outcomes in orthopedic surgery. However, the effect of delayed surgery on patient-reported outcomes (PROs) in those undergoing anterior cruciate ligament reconstruction (ACLR) remains unknown. The purpose of this study was to compare achievement of clinically significant outcomes (CSOs) in patients with greater than six months of time from injury to ACLR to those with less than or equal to six months of delay to surgery. Methods: A retrospective cohort study was performed to identify all patients undergoing primary ACLR between January 2017 and January 2018, with a minimum follow-up of one year. Patient demographics, comorbid medical conditions, and outcome scores on the International Knee Documentation Committee (IKDC) score and the Knee Injury and Osteoarthritis Outcomes (KOOS) Score were compared between patients with greater than six months from time of injury to ACLR and those with less than six months. CSOs were defined using minimal clinically important difference (MCID), patient acceptable symptomatic state (PASS), and substantial clinical benefit (SCB). Multivariate logistic regression was performed to produce odd ratios (OR) for outcome achievement and Weibull parametric survival analysis was performed to produce hazard ratios (HR) for relative time to outcome achievement. CSOs and time to CSOs at 1- and 2-year follow-ups were compared. Results: A total of 416 patients were included, with an average age of 34.7±14.4 years; 154 (37%) patients sustained ACL injury greater than six months prior to surgery. On multivariate analysis, these patients had significantly reduced likelihood to achieve the SCB on the KOOS Sport (OR: 0.2, 95% CI: 0.05-0.98, P = 0.04), PASS on the IKDC (OR: 0.58, 95% CI: 0.40-0.82, P = 0.03) and KOOS Pain (OR: 0.68, 95% CI: 0.49-0.93, P = 0.002), as well as greater likelihood to undergo revision ACLR (OR: 8.99, 2.28-30.36, P < 0.001) at 1-year follow-up. At 2-years follow-up, patients with greater than 6 months of time from injury to ACLR> 6 months similarly experienced significantly reduced likelihood to achieve the PASS on the IKDC (OR: 0.15, 95% CI: 0.05-0.43, P < 0.001), KOOS Sport (OR: 0.38, 95% CI: 0.16-0.85, P = 0.02), KOOS Pain (OR: 0.31, 95% CI: 0.13-0.68, P = 0.012), KOOS Symptoms (OR: 0.32, 95% CI: 0.14-0.69, P = 0.004), KOOS activities of daily living (ADL) (OR: 0.05, 95% CI: 0.00-0.85, P = 0.04), and a greater likelihood to undergo revision ACLR (OR: 8.34, 95% CI: 3.51-11.4, P = 0.001). Finally, patients with delayed ACLR experienced delayed achievement of multiple CSOs on time-to-event analysis (HR: 1.55-6.48). No impact of surgical timing on achievement of the MCID was observed. Conclusion: Patients with greater than 6 months from time of injury to ACLR reported inferior PROM scores, reduced likelihood to achieve CSOs, and increased rates of revision surgery at 1-year and 2-years follow-up. These patients also reported significantly delayed achievement of CSOs. This information should be offered during preoperative counseling to illustrate the potential risk of delayed surgery in active patients with acute ACL rupture. Table 1. PROM Scores at 1-year Follow-up ≤6m to ACLR >6m to ACLR P-Value Preoperative Scores N=262 N=154 IKDC 48.2±17.2 47.5±17.8 0.75 KOOS JR 65.5±16.4 62.5±16.5 0.15 KOOS Pain 63.8±21.4 61.6±20.4 0.32 KOOS Sx 62.5±19.9 59.2±20.6 0.13 KOOS ADL 72.9±23.1 70.9±22.4 0.42 KOOS QoL 27.9±21.1 23.6±21.8 0.06 KOOS Sport 33.3±26.6 32.7±25.8 0.82 KOOS PS 34.6±15.3 36.2±14.3 0 Postoperative Scores IKDC 81.8±17.6 57.9±22.3 <0.001 KOOS JR 87.3±10.5 63.2±20.2 <0.001 KOOS Pain 86.3±11.2 66.7±19.4 <0.001 KOOS Sx 86.4±12.5 64.6±24.0 <0.001 KOOS ADL 96.3±10.1 77.0±19.4 <0.001 KOOS QoL 71.4±22.3 38.3±27.7 <0.001 KOOS Sport 83.5±17.5 44.0±30.2 <0.001 KOOS PS 10.4±8.0 33.4±16.5 <0.001 IKDC: International Knee Documentation Committee; KOOS: Knee Injury and Osteoarthritis Outcome Score; JR: joint reconstruction; Sx: symptoms; ADL: activities of daily living; QoL: quality of life; PS: physical symptoms; ACLR anterior cruciate ligament reconstruction Table 2. Relationship between Symptom Duration and Outcomes at 1-year Follow-Up Odds Ratio (95% CI) P-Value (Univariate) P-Value (Multivariate) SCB KOOS Sport 0.2 (0.05-0.98) 0.01 0.04 PASS IKDC 0.58 (0.40-0.82) 0.003 0.03 PASS KOOS Sport 0.59 (0.42-0.83) 0.003 0.48 PASS KOOS Pain 0.68 (0.49-0.93) 0.02 0.002 PASS KOOS Symptoms 0.39 (0.06-2.12) 0.03 0.27 PASS KOOS ADL 0.59 (0.03-0.93) 0.01 0.7 Revision ACLR 8.99( 2.28-30.36) 0.002 0.001 IKDC: International Knee Documentation Committee; KOOS: Knee Injury and Osteoarthritis Outcome Score; ADL: activities of daily living; ACLR: anterior cruciate ligament reconstruction; SCB: substantial clinical benefit; PASS: patient acceptable symptomatic state Table 3. Relationship between Symptom Duration and Outcomes at 2 Years Follow-Up Odds Ratio (95% CI) P-Value (Univariate) P-Value (Mulitvariate) SCB KOOS QoL 0.43 (0.18-0.96) 0.04 0.5 PASS IKDC 0.15 (0.05-0.43) <0.001 <0.001 PASS KOOS Sport 0.38 (0.16-0.85) 0.02 0.020 PASS KOOS Pain 0.31 (0.13-0.68) 0.009 0.004 PASS KOOS Symptoms 0.32 (0.14-0.69) 0.01 0.004 PASS KOOS ADL 0.05 (0-0.85) 0.008 0.04 Revision ACLR* 8.34 (3.51-11.4) 0.07 0.001 *Multivaraite logistic regression was performed for revision ACLR as P-value on univariate testing approached 0.05